Văn học Việt Nam thế kỷ XX - Phan, Cự Đệ (Văn học, 2004)
Giới thiệu truyện ngắn của nhiều tác giả:Vũ Thị Thường, Đỗ Quang Tiến, Trần Kim Trắc, Nguyễn Thị Ngọc Tú, Nguyễn Tuân, Nhật Tuấn, Phan Tứ, Chu Văn